2021
DOI: 10.3390/ma14185324
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Spray-Dried and Reconstituted Flaxseed Oil Cake Extract as Encapsulating Material and Carrier for Probiotic Lacticaseibacillus rhamnosus GG

Abstract: Agro-industrial by-products are promising source of biopolymers, including proteins and polysaccharides. This study was designed to evaluate the flaxseed oil cake extract (FOCE) as natural encapsulating material and carrier for probiotic Lacticaseibacillus rhamnous GG (LGG). The powders were obtained using three spray drying inlet temperatures (110 °C, 140 °C, 170 °C), and reconstituted. The influence of temperature on water activity, morphology, chemical composition, flowability and cohesiveness of the powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…The results of this study agree with those of Matwijczuk et al [22] and L. Svečnjak, D. Bubalo, G. Baranović, and H. Novosel [54]. Łopusiewicz et al [53] and Matwijczuk et al [22] also reported that the vibration at 3300-3200 cm −1 , which belongs to the irregular absorption of carboxylic acid (with a wide -OH band) while enhancing the stretching vibration of the C-H group and the wide band of vibration, is due to the strong hydrogen bonding of carboxylic acid dimer [55]. The regions of 3000-2800 cm −1 were characterized by stretching vibrations of the C-H groups.…”
Section: Physicochemical Characterization Of Umami-rich Seasoning Powdersupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study agree with those of Matwijczuk et al [22] and L. Svečnjak, D. Bubalo, G. Baranović, and H. Novosel [54]. Łopusiewicz et al [53] and Matwijczuk et al [22] also reported that the vibration at 3300-3200 cm −1 , which belongs to the irregular absorption of carboxylic acid (with a wide -OH band) while enhancing the stretching vibration of the C-H group and the wide band of vibration, is due to the strong hydrogen bonding of carboxylic acid dimer [55]. The regions of 3000-2800 cm −1 were characterized by stretching vibrations of the C-H groups.…”
Section: Physicochemical Characterization Of Umami-rich Seasoning Powdersupporting
confidence: 92%
“…Other properties of the powders, such as bulk and tapped densities, were significantly different (p < 0.05) as measured for the umami-rich seasoning powders obtained for each run condition, ranging from 0.40-0.63 (g/cm 3 ) and 0.43-0.69 (g/mL), respectively (Table 3). Additionally, the inlet temperature rises, and the water evaporates rapidly, which forms the shell on the particle's surface instantly, whereby the water vapor inside the particle will be released from the pores due to high pressure, which will lead to decreased bulk density [29,31,53]. Unfortunately, it was impossible to compare the differences in powder densities owing to the different drying methods used in this study and the commercially available products mentioned above.…”
Section: Physicochemical Characterization Of Umami-rich Seasoning Powdermentioning
confidence: 99%
“…A similar morphology of powders was observed by Bustamante et al when mucilages (from chia and flaxseed), as well as inulin, were used as encapsulating agents [ 17 ]. In our previous studies, a more wrinkled and folded morphology was observed when Flaxseed Oil Cake Extract was subjected to spray-drying [ 16 , 39 ]. In contrast, a spherical shape with holes and a very collapsed morphology was observed in spray-dried whey protein isolate powders, which can be linked with the surface activity of whey protein [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, camelina is abundant i sential amino acids (such as leucine, valine, phenylalanine, lysine, isoleucine) [35], the favorable amino acid content can induce a synergistic effect for LAB growth and m CPC an excellent matrix for fermentation. Moreover, camelina is also capable of pro ing mucilage, which can be used as a prebiotic material and carrier for bacteria actin a prebiotic [11,36]. Table 1 presents the results of the pH, titratable acidity (TA) and total solids content (TSC) measurements during the storage time.…”
Section: The Changes In Ph Ta Tsc Lab Viability and Colormentioning
confidence: 99%